أهمية الحديث الضعيف ودروره في التشريع والإعجاز العلمي - Alabas, Tajuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2021)
This research paper highlights the importance of understanding the term hadith. Especially the term hadith dhaif, which is still confusing today. Hadith dha'if sometimes relied on hadith maudhu’ so have to be careful in understanding both. Some of them follow the Sunnah and hadith scholars as a whole, because they violate their consensus and reject the weak absolutely. And some of them mistakenly state that the consensus of the hadith scholars is not to hold on the hadith dha'if in various laws. This study confirms the importance of understanding the term hadith dha'if. Apart from that, the positive effects are numerous, especially on the enrichment of jurisprudence and history, biographies and metaphors. Indeed, modern science in our time has declared the validity of the texts of many hadith dha'if, for example in discussions of scientific miracles, so we must pay attention to these hadith dha'if. There has been so much research into the branches of the faith and its virtues, and issues of jurisprudence, and ethics, that scholars have attempted to find Hadith shahihc and hadith hasan. However, when there were no sahih and hasan hadiths, they had hadiths dha'if. Researcher's approach in this research is an inductive approach: extrapolating the importance of hadith dha’if and its role in law and scientific studies. The analytical method is to analyze what will be collected from the hadiths, atsar and aqwalu ‘ulama. . Each of the two approaches works to embody and illustrate the importance of the hadith dha’if and its role in law and scientific studies.